PENGUJIAN MODEL HUBUNGAN KEPUASAN KERJA DAN PERILAKU MENYIMPANG DI TEMPAT KERJA DITINJAU DARI KARAKTERISTIK DEMOGRAFI - Isthofaina Astuty; Gita Danupranata (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2021)
This study aims to identify the effect of job satisfaction on deviance workplace behavior (DWB) in terms of education level and age aspects of employees at Muhammadiyah University of Yogyakarta. The sample used was 118 employees from faculty and bureau level work units in the Muhammadiyah University of Yogyakarta. In this study, the variable job satisfaction was measured by a questionnaire from S.Crow, et al (2012) which consisted of 6 question items with indicators of satisfaction, reward, involvement and job appraisal. The DWB variable refers to the behavior of organizational members who tend to consciously violate organizational rules. This variable is measured by a questionnaire from Robinson and Bennett (1995) which consists of 19 question items. In this questionnaire, DWB is measured by four dimensions, namely production deviations, property deviations, political storage and individual aggression. The results of the analysis tool using multiple regression with dummy variables indicate that; 1) job satisfaction has a negative effect on deviant behavior at work, 2) there is a difference in the effect of job satisfaction on DWB for employees who have high and low levels of education, 3) there is a difference in the effect of job satisfaction on DWB for young and old employees.